Friends or foes? The impact of voluntary sustainability standards on agricultural exports of developing countries - Marcelo Dolabella; Mario Saeteros (Inter-American Development Bank (IDB), 2024)
Private actors have been actively working on standards that certify products and their production processes to minimize negative externalities. The number of Voluntary Sustainability Standards (VSS) has been increasing over the last few decades, raising interest in understanding their impact on trade flows. Standards governing the production of agricultural commodities are especially crucial for developing countries as these goods often constitute a significant portion of their exports. Using a structural gravity model, we investigate how VSS certification affects exports for developing countries across eight highly traded commodities, and twelve VSS certification schemes from 2013 to 2021. Our analysis highlights how these effects differ for Latin America and the Caribbean compared to the rest of the world. The results indicate a positive and significant effect of VSS certification on exports, with on average a one percent increase in VSS coverage, resulting in a 1.86% increase in export value. We observed positive and significant impacts on bananas, palm oil, tea, and cotton exports. Our findings also suggest that trade gains are larger for lower-income exporters trading with high-income destinations, suggesting an important role of VSS in reducing information asymmetries. Also, we observe that the proliferation of standards might reduce the positive effects associated with VSS adoption for the main agricultural producers.
Keywords: F18; Q17; Q18; Q56; 330; Voluntary sustainability standards; private standards; international trade; developingcountries; Latin America and the Caribbean